Review of Palpostilpnus Aubert (Hymenoptera, Ichneumonidae, Phygadeuontinae), with the description of ten new species - Reshchikov, Alexey; Santos, Bernardo F.; Liu, Jing-Xian; Barthélémy, Christophe (European Journal of Taxonomy, 2019)
The taxonomic limits of Palpostilpnus Aubert, 1961 are reviewed. The genus is characterized mainly by having a very elongated maxillary palp; head short and depressed, with mandible small and with distinct basal groove; ovipositor short and slender, needle-like. A total of seventeen species are recognized, of which ten are described as new: P. aki sp. nov., P. angka sp. nov., P. angkor sp. nov., P. hainanensis sp. nov., P. mangrovi sp. nov., P. pterodactylus sp. nov., P. ranui sp. nov., P. singaporensis sp. nov., P. tamasek sp. nov. and P. trifolium sp. nov. The combination Palpostilpnus rufinator (Aubert, 1961) stat. rev. is proposed. An illustrated key to the known species of the genus is provided.